REKONSTRUKSI PSIKOANALISIS HUMANIS DIALEKTIK ERICH FROMM DALAM PENDIDIKAN PESANTREN - Theguh Saumantri; Jefik Zulfikar Hafizd (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2022)
Islamic Boarding School as an educational institution makes a great contribution in the field of religion. Education in Islamic Boarding School considers that man is privileged with the ability to think to understand the universe, himself, and the signs of God's majesty. Erich fromm’s view man is actually an organism (living thing) in him there is a process of energy or passions that encourages satisfaction in the around world. If viewed in the perspective of Islamic Boarding School education, santri as a human being who is in an existential dilemma who is experiencing confusion and trying to find a way to overcome the existential problem. More spiritually Islamic Boarding School education is needed and has a role in this problem. Erich Fromm in his Dialectical Humanistic theory gives a view that the man who is in existence has basic needs and character. The purpose of this study is to examine the thinking of erich fromm as a paradigm of human existence that never ceases to be dialectic in the world of reality of its life. The methodology in this research is a library research method, which examines literature sources regarding the thoughts of figures and research objects contained in books, journals, or articles. The results of this study illustrate that humans in this case who pursue islamic boarding school education should be given a guide to be critical in terms of learning or in matters concerning humanity. Because in the view of Dialectical Humanist Theory erich fromm is actually a critical attitude towards human problems, which is to try to relax things that look out of line (opposite) and find solutions. Through education, learners or students will be able to recognize themselves and those around them by understanding their uniqueness.